KEPENTINGAN AMERIKA SERIKAT MENGAJUKAN EKSTRADISI ATAS TRANSNATIONAL CYBERCRIME KASUS “WELCOME TO VIDEO” - Tasya Yonetha Mansjoer; Miko Aditiya Suharto (HUKMY : Jurnal Hukum, 2025)
The United States Internal Revenue Service (US-IRS) discovered a crypto transactions on the child pornography trafficking site "Welcome to Video" which led to the arrest of Son Jong Woo, a South Korean national as the administrator of the site, and the arrest of several other site users in several countries. This study aims to determine the United States national interest in submitting extradition request for Son Jong Woo to South Korea. This study uses normative legal research methodology. This study concludes that the urgency of the United States to request the extradition to South Korea is based on the authority possessed by the United States to prosecute Son Jong Woo with the consideration based on the analysis of locus delicti, the characteristic of the crime, and extraterritorial jurisdiction on transnational cybercrime in the Welcome to Video case.